Magnetic Supraparticles: A Single Magnetic Particle with Nearly Unlimited Encoding Options (Small 28/2021). Issue 28 (15th July 2021) - Müssig, Stephan; Reichstein, Jakob; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl
Abstract : In article number 2101588, Karl Mandel and co‐workers report on how to obtain a micron‐sized magnetic supraparticle which carries a unique magnetic code. Via a hierarchical particle assembly principle, using magnetic nano building blocks, a nearly unlimited number of encoding options can be achieved. The particles enable magnetic tagging and tracing for recycling and anti‐counterfeiting applications.